Linker Design Impacts Antibody-Drug Conjugate Pharmacokinetics and Efficacy via Modulating the Stability and Payload Release Efficiency - Su, Dian; Zhang, Donglu (Frontiers in Pharmacology, 2021)
The development of antibody-drug conjugates (ADCs) has significantly advanced in the past decade. The advancement of ADCs has been facilitated by advancements of payloads, linkers and conjugation methods. In particular, linker design plays a critical role in modulating ADC stability in the systemic circulation and payload release efficiency in the tumors, which thus affects ADC pharmacokinetic (PK), efficacy and toxicity profiles. We have investigated key linker parameters such as conjugation chemistry (e.g., maleimide vs disulfide), linker length and linker steric hindrance and their impacts on PK and efficacy profiles. Herein, we discuss our perspectives on development of integrated strategies for linker design to achieve a balance between ADC stability and payload release efficiency for desired efficacy in antigen-expressing xenograft models. The strategies have been successfully applied to the design of site-specific THIOMABTM antibody-drug conjugates (TDCs) with different payloads. We also propose to conduct dose fractionation studies to gain guidance for optimal dosing regimens of ADCs in pre-clinical models.